A The Use of Wokwi Learning Media Can Increase Science Learning Outcomes in Madrasah Ibtidaiyah Students - Wahab, Abdul; Suherli, Zulmiswal; Fitriati, Resti; Salsabila (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, Jurusan Tarbiyah dan Keguruan, Sekolah Tinggi Agama Islam Negeri Majene, 2025)
This study aims to: (1) examine students' science learning outcomes before using Wokwi; (2) assessing learning outcomes after the use of the media; and (3) measuring the improvement of learning outcomes obtained. This study uses a quantitative method with a pre-experimental design of one-group pretest-posttest to measure changes in student learning outcomes after the use of Wokwi learning media. The research population is all students of class VI MIN 2 Majene for the 2025/2026 school year as many as 22 people, all of whom were used as samples with saturated sample techniques. Data was collected through learning outcome tests in the form of 20 multiple-choice questions that included aspects of knowledge, understanding, and application of concepts, given in the form of pretests and posttests. Data analysis was carried out with descriptive statistics to describe the average student achievement and N-gain calculation to determine the level of improvement in learning outcomes more measurably after the treatment was given. The results showed that (1) students' science learning outcomes before the use of Wokwi media were in the medium and high categories with an average of 58.45, which shows the limitations of their initial understanding. (2) After the implementation of Wokwi, the average score increased significantly to 82.73 with the distribution of the majority score in the high and very high categories, without any students in the medium or low categories. (3) The calculation of N-gain of 0.57 which is classified as moderate shows that 75% of students experienced moderate improvement, 20% high, and only 5% low. These findings prove that Wokwi media is effective in improving science learning outcomes while leveling student achievement, although further development is still needed through simulation variations and integration with collaborative and project-based learning methods.